Political Intervention in Post-Reform State Official Recruitment - Saiful Anam; Cakra Heru Santosa; Fahririn Fahririn; Muhammad Fachrul Hudallah; Regita Widya Prameswari (Universitas Lampung, 2026)
The recruitment of state officials in post-reform Indonesia remains vulnerable to political intervention, which can undermine the independence of public officials and contribute to corruption, collusion, and nepotism. This study employs a normative juridical approach to examine the political dynamics of state official recruitment and identify measures to reduce political interference. The findings indicate that strengthening merit-based recruitment, limiting political influence, and implementing comprehensive legal and institutional reforms based on the theories of Max Weber and Lawrence M. Friedman are essential to promoting professional, transparent, and accountable governance in Indonesia.